A Facility Layout Planner Tool Based on Genetic Algorithms - Eugénio Oliveira (2016)
Nowadays, in order to maintain their competitiveness, manufacturing companies must adapt their production methods quickly, with minimum expenditure, to frequent variations on demand. With the shortage of the product life time, flexibility, efficiency and reusability of industrial processes are important factors, which may determine the survival of the company. The ReBORN project is working around these ideas, namely studying how can an old production equipment be reused into new contexts. The ReBORN Workbench is a simulation tool for factory layout design, which generates solutions based on the production requirements and facilities' availability, corresponding Life Cycle Assessment, and associated location cost. This paper is concerned with the ReBORN Workbench module responsible to generate solutions for equipment location, generally know as Facility Layout Problems. A Genetic Algorithm was implemented to solve these problems, which aims to minimize the total material handling costs. The effectiveness of the proposed approach is evaluated with a numerical example and compared with other similar approaches. The results show that the proposed approach is indeed effective to solve problems regarding facilities layout.